2008
DOI: 10.1111/j.1471-0528.2008.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum bleeding of unknown origin in the second half of pregnancy and pregnancy outcomes

Abstract: Objective  The purpose of our investigation was to evaluate factor(s) associated with unexplained antepartum bleeding of unknown origin (ABUO) after 24 weeks of pregnancy and correlate unexplained haemorrhage with maternal and perinatal outcomes.Design  This is a retrospective observational study.Setting  King Edward Memorial Hospital (KEMH), Subiaco, Western Australia.Population  Singleton pregnancies delivering at KEMH between January 1998 and December 2004.Methods  ABUO was defined as bleeding after 20 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 9 publications
2
28
0
Order By: Relevance
“…[5][6][7][8][9][10] Similarly, the results of studies conducted by Berkowitz et al, Signore et al, and Sipila et al [13][14][15] were also in agreement with the results of this study, which showed that women with ABUO were more than twice as likely to have preterm delivery. Applying Hill's criteria of causality, we can therefore say that at least in the case of preterm delivery, the association is likely to be causal.…”
Section: Comparison With Literaturesupporting
confidence: 92%
See 4 more Smart Citations
“…[5][6][7][8][9][10] Similarly, the results of studies conducted by Berkowitz et al, Signore et al, and Sipila et al [13][14][15] were also in agreement with the results of this study, which showed that women with ABUO were more than twice as likely to have preterm delivery. Applying Hill's criteria of causality, we can therefore say that at least in the case of preterm delivery, the association is likely to be causal.…”
Section: Comparison With Literaturesupporting
confidence: 92%
“…This was supported by the results of McCormack et al, 10 who showed an elevated risk of induction at term among women with ABUO. Although it is difficult to be certain that the reason for induction of labour was mainly ABUO, adjusting for confounding factors should have addressed this uncertainty.…”
Section: Comparison With Literaturesupporting
confidence: 66%
See 3 more Smart Citations